2007
DOI: 10.1074/jbc.m611817200
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat Increases Cyanide-insensitive Respiration in Murine Lung Epithelial Cells by Activating an NAD(P)H:Paraquat Oxidoreductase

Abstract: Pulmonary fibrosis is one of the most severe consequences of exposure to paraquat, an herbicide that causes rapid alveolar inflammation and epithelial cell damage. Paraquat is known to induce toxicity in cells by stimulating oxygen utilization via redox cycling and the generation of reactive oxygen intermediates. However, the enzymatic activity mediating this reaction in lung cells is not completely understood. Using self-referencing microsensors, we measured the effects of paraquat on oxygen flux into murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 72 publications
1
50
0
Order By: Relevance
“…In a recent study with lung cells, paraquat was shown to cause a 2-4 fold increase in cellular oxygen consumption, which was neither due to NADPH oxidase nor mitochondrial respiration (Gray et al, 2007). This study further indicated the presence of a specific NADPH:paraquat oxidoreductase in the lung cells for initiating the redox mechanism (Gray et al, 2007). Whether similar mechanism exists in microglial cells is not known and remains to be investigated.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In a recent study with lung cells, paraquat was shown to cause a 2-4 fold increase in cellular oxygen consumption, which was neither due to NADPH oxidase nor mitochondrial respiration (Gray et al, 2007). This study further indicated the presence of a specific NADPH:paraquat oxidoreductase in the lung cells for initiating the redox mechanism (Gray et al, 2007). Whether similar mechanism exists in microglial cells is not known and remains to be investigated.…”
Section: Discussionmentioning
confidence: 63%
“…Our results support the hypothesis that intricate mechanisms regulate different pools of ROS in cells and in paraquat cytotoxicity, and the pool of ROS produced by NADPH oxidase is an early event preceding production of mitochondrial ROS and cell death. In a recent study with lung cells, paraquat was shown to cause a 2-4 fold increase in cellular oxygen consumption, which was neither due to NADPH oxidase nor mitochondrial respiration (Gray et al, 2007). This study further indicated the presence of a specific NADPH:paraquat oxidoreductase in the lung cells for initiating the redox mechanism (Gray et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Low levels of nitrofurantoin redox cycling activity were also evident in cytosolic fractions of MLE 15 cells, suggesting that additional enzymes also redox cycle nitrofurantoin in these cells. In this regard, our laboratory has recently demonstrated paraquat redox cycling by thioredoxin reductase in cytosolic fractions of MLE 15 cells [40]. Studies to identify the NADPH oxidoreductases that are important in redox cycling nitrofurantoin in the cytosolic fraction of cells are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, we demonstrated that the cytoplasm of lung epithelial cells is a rich source of enzymes capable of mediating chemical redox cycling (20). One important enzyme involved in this process is thioredoxin reductase, a homodimeric flavoprotein that catalyzes the reduction of oxidized thioredoxin, as well as other redox-active proteins, and plays a key role in maintaining cellular redox homeostasis (20,21).…”
mentioning
confidence: 99%